SPECIFIC FEATURES IN THE EXPRESSION OF INTRASPECIES VARIABILITY OF PRUNUS PUMILA FRUITS IN CHELYABINSK PROVINCE IN THE PROCESS OF INTRODUCTION - M. S. Lezin; V. S. Simagin; A. V. Lokteva (Труды по прикладной ботанике, генетике и селекции, 2019)
Background. The studied population of Prunus pumila L. has been introduced into Chelyabinsk Province, as its natural area of distribution is in North America. Of interest for researchers is the introduced population’s variability, induced by the effect of soil and climate factors natural for its new habitat.Materials and methods. A collection of 197 plants was employed to study the variability of P. pumila. Morphological characters were described in compliance with atlases dedicated to seed and fruit descriptive morphology, with some adjustments concerning specific features of the subfamily Prunoideae Focke. The confidence interval for means was calculated using the reliability criterion of t2 = 2.576. The degree of variation was assessed for the studied characters according to S. A. Mamaev’s scale.Results and conclusion. The average fruit weight was 2.49±0.11 g and varied from 1.25 to 5.15 g. The average stone weight was 0.25±0.01 g. Out of the number of morphometric traits, almost all linear characters of fruit and stone size had low variability (coefficient of variation [V]: 8–12%). Of those linear characters, only the peduncle length showed medium variability (V = 13–20%). The stone weight also had medium variability, while the fruit weight demonstrated high variability (V = 21–30%). The fruit shape was subglobose (40.3%), less frequently ovate (20.9%), ovoid (20.9%), broadly ovoid (9.7%), cordate (6.1%) or elliptic (2.0%). The ventral suture was usually barely noticeable, less frequently moderately (3.1%) or strongly expressed (1.0%). Polymorphism was observed in the pulp color, which was usually green-pink (72.8%). The P. pumila stone shape was elliptic (38.1%) or subglobose (34.0%), less frequently prolate (10.7%), ovoid (13.2%) or obovate (4.1%). The stone was symmetrically shaped from the ventral suture and sides, usually looking subglobose from the sides. The shape of the stone’s apex was rounded (85.3%) or, less frequently, obtusely mucronate (15.7%); its base was rounded (80.7%), often attenuate (15.7%), less frequently slightly slanted (3.6%). The stone surface texture was smooth (57.4%), often slightly costate (36.5%). There were several cases of a more costate surface of the stone (6.1%). Thus, the introduced population was found to have broad polymorphism of morphological characters in the fruit and the stone. A considerable increase was observed in morphometric indicators, including the size of fruit and stone, compared with those typical for the species in natural environments, which may be of special significance for breeders. The fusiform shape of the stone, characteristic of var. depressa Pursh. in its natural habitat, was absent in the introduced population.